GCG SEBAGAI VARIABEL MODERASI: CSR, IOS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - SURYADI, NANDA; KUSDIANA, YAYU; YUSNELLY, ARIE (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
This study aims to determine Good Company Governance (GCG) as a moderation variable: Corporate Social Responsibility (CSR), Investment Opportunities Set (IOS) and Capital Structure against the value of state - owned companies listed on the IDX in 2018-2022. Data analysis techniques using Partial Least Square (PLS) method. This study used causality research design. The results of the measurement and disclosure of CSR, capital structure and GCG do not affect the value of the company. However, IOS has a positive impact on the value of the company. GCG can moderate the relationship between CSR and capital structure on the value of the company. Unlike GCG, which cannot moderate the interaction between IOS and company values.